Status of cerebrovascular autoregulation relates to outcome in severe paediatric head injury: STARSHIP, a prospective multicentre validation studyResearch in context - Shruti Agrawal; Claudia Smith; Stefan Y. Bogli; Michal M. Placek; Manuel Cabeleira; Deborah White; Esther Daubney; Adam Young; Erta Beqiri; Riaz Kayani; Diarmuid O'Donnell; Nazima Pathan; et al. (EClinicalMedicine)
Summary: Background: Continuous assessment of cerebral autoregulation (CA) using pressure reactivity index (PRx), is a promising tool for individualized management to improve outcome after traumatic brain injury (TBI). However, experience with CA in paediatric TBI (pTBI) is limited to retrospective or single-centre studies. Methods: Studying Trends of AutoRegulation in Severe Head Injury in Paediatrics (STARSHIP) (clinicalTrials.gov identifier-NCT0688462), was a prospective, multicentre, observational, research database study conducted across 10 identified UK Paediatric Intensive Care Units from 01.07.2018 till 31.04.2024. The main objective was to validate and identify optimal thresholds of PRx associated with outcome (as assessed with Glasgow outcome scale extended for Pediatrics at 12 months) in children (<16 years) requiring invasive arterial blood pressure and intracranial pressure monitoring for TBI and establish a comprehensive research database. Apart from high-resolution data, clinical and outcome data up to 12 months post-ictus were collected. Univariable and multivariable analyses including propensity score matching, were employed to determine the effect of PRx on outcome whilst considering covariates, centre-specific differences and other multimodal metrics. Findings: Out of 153 recruited, 135 children (median age 96 months) with consent and adequate data were included. Overall median PRx of the cohort was −0.09 (IQR −0.19 to 0.08). Both ICP and PRx were elevated in non-survivors and children with unfavourable outcome. PRx retained a significant effect on outcome after adjusting for various clinical and monitoring variables. The critical PRx threshold identified were 0.5 for mortality and 0.0 for favourable outcome. Interpretation: With STARSHIP, we validate the outcome association of CA derangements as assessed by PRx in pTBI in the first prospective observational multicentre study. This provides additional evidence for the potential use of PRx for individualizing prognosis and treatment and pave way for further research in pTBI with the created database. Funding: This study was funded by Action Medical Research for Children's Charity and Addenbrookes Charitable Trust, UK (Grant number-GN2609). Cambridge University Hospitals is the study sponsor (Reference: A094693, contact person: Michelle Ellerbeck-michelle.ellerbeck@nhs.net).